Effect of different evasion maneuvers on anticipation and visual behavior in elite rugby league players - Connor, J. D.; Crowther, R. G.; Sinclair, W. H. (Motor control, 2018)
This study examined the anticipation and visual behavior of elite rugby league players during two different evasion maneuvers (side- and split-steps). Participants (N=48) included elite rugby league players (n=38) and controls (n=10). Each participant watched videos consisting of side- and split-steps, and anticipation of movement and eye behavior were measured. No significant differences between the groups or evasion maneuvers were found. The split-step was significantly harder to predict. Elite players appeared to spend more time viewing the torso and mid-region of the body compared with the controls. ABSTRACT FROM AUTHOR